Outcomes of preoperative chemoradiotherapy followed by surgery in patients with unresectable locally advanced sigmoid colon cancer. Issue 1 (December 2016) - Qiu, Bo; Ding, Pei-Rong; Cai, Ling; Xiao, Wei-Wei; Zeng, Zhi-Fan; Chen, Gong; Lu, Zhen-Hai; Li, Li-Ren; Wu, Xiao-Jun; Mirimanoff, Rene-Olivier; Pan, Zhi-Zhong; Xu, Rui-Hua; et al.
Abstract Background Complete resection of locally advanced sigmoid colon cancer (LASCC) is sometimes difficult. Patients with LASCC have a dismal prognosis and poor quality of life, which has encouraged the evaluation of alternative multimodality treatments. This prospective study aimed to assess the feasibility and efficacy of neoadjuvant chemoradiotherapy (neoCRT) followed by surgery as treatment of selected patients with unresectable LASCC. Methods We studied the patients with unresectable LASCC who received neoCRT followed by surgery between October 2010 and December 2012. The neoadjuvant regimen consisted of external-beam radiotherapy to 50 Gy and capecitabine-based chemotherapy every 3 weeks. Surgery was scheduled 6–8 weeks after radiotherapy. Results Twenty-one patients were included in this study. The median follow-up was 42 months (range, 17–57 months). All patients completed neoCRT and surgery. Resection with microscopically negative margins (R0 resection) was achieved in 20 patients (95.2%). Pathologic complete response was observed in 8 patients (38.1%). Multivisceral resection was necessary in only 7 patients (33.3%). Two patients (9.5%) experienced grade 2 postoperative complications. No patients died within 30 days after surgery. For 18 patients with pathologic M0 (ypM0) disease, the cumulative probability of 3-year local recurrence-free survival, disease-free survival and overall survival was 100.0%, 88.9% and 100.0%, respectively. For all 21 patients, the cumulative probability of 3-year overall survival was 95.2% and bladder function was well preserved. Conclusion For patients with unresectable LASCC, preoperative chemoradiotherapy and surgery can be performed safely and may result in an increased survival rate.